The effect of glass addition and the grain diameters on dielectric properties of CaCu₃Ti₄O₁₂ (CCTO) / Masturah Mohamed - Mohamed, Masturah (2016)
Calcium copper titanate, CaCu₃Ti₄O₁₂ (CCTO)is well known to have colossal dielectric constant in the range of 10⁵. This phenomenon was reported to have a strong dependence on doping condition and processing method. However, while exhibiting high dielectric constant, CCTO also shows a high dielectric loss. This has motivated researchers to conduct several studies in improving the final dielectric characteristic of CCTO. Two separate studies on the effect of doping concentration and the effect of processing method on dielectric properties of CCTO were conducted. For the first part, two types of glasses; electrical conducting V₂O₅₋TeO glass (VT) and ionic conducting PbO-B203 glass (PB), were added into CCTO. Both composites were prepared by conventional solid-state synthesis method. X-ray diffraction (XRD) analysis showed single phase CCTO was obtained with no traces of crystalline phase related to both VT and PB glass. For the first addition; (1-x) CCTO - (JC) VT [x, wt.%=0.03, 0.05, 0.10], the scanning electron microscopy (SEM) study showed that low melting point VT glass addition facilitated the grain growth of CCTO...